Model Integrasi Quality Control Pascapanen Berbasis Teknologi Dalam Meningkatkan Mutu Wortel (Daucus Carota L.): A Systematic Literature Review - Andini Rosady; Namara Cinta Adzani; Mochammad Fadly; Ahmad Yassin Firmansyah; Uding Sastrawan (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Carrot (Daucus carota L.) is a horticultural commodity with high economic value whose quality is strongly influenced by postharvest handling in maintaining its physical, chemical, and microbiological characteristics. Major postharvest problems include continuous respiration and transpiration processes, mechanical damage, and microbial contamination that lead to weight loss, reduced freshness, and shorter shelf life. This study aims to analyze the effect of postharvest handling on carrot quality, identify factors causing quality deterioration, and evaluate the implementation of quality control and the potential integration of technology in quality assurance systems. The method used was a literature review by examining scientific articles from the last five years obtained from online databases and analyzed using content analysis techniques. The results indicate that low temperature storage (0°C) and high relative humidity (±95%) effectively reduce respiration rate and water loss. The implementation of quality control through sorting, grading according to SNI 3163:2014, sterilization, packaging, labeling, and standardized distribution improves product quality consistency. Technological integration such as ozonization, edible coating, cold atmospheric plasma, and Internet of Things (IoT)-based monitoring provides synergistic effects in extending shelf life and improving product safety. In conclusion, an integrated approach combining conventional methods and technological innovation is an effective strategy to maintain and improve carrot quality within modern supply chains.